CONTEMPORARY POSSIBILITIES OF TREATING VASOFORMATIVE TISSUE TUMOURS - Justova, Eva; Pazdera, Jindrich; Mihal, Vladimir (Biomedical papers, 2000)
The authors present a review of up-to-date methods of vasoformative tissue tumours treatment. The necessity tochoose the best therapy and the risks of single therapeutical procedures are pointed out.
Keywords: Vasoformative tissue tumours / Haemangiomas / Therapy